Prevelance of Taxoplasma gondiiantibodies in healthy pregnant women and pregnant women with a bad obstetriac history in Sri Lanka - Samarasinghe, S (My University, 1999)
A prospective follow-up study was carried out among different categories of pregnant women in Sri Lanka,to establish seroprevalence rates in this group,to examine the possible role of toxoplasma gondii infection among women with bad obstetric histories,and to examine the relationship between seroprevalence and various known risk factors for infection.The result of this study indicate that although toxoplasmosis is of relatively low endemicity in sri lanak, it still poses a significant problems to pregnant women,and may contribute towards the occurrence of sporadic single abortions.It does not appear to be associated with a bad obstetric history,but confirmation of this will require further studies.